Age‐dependent determinants of antipsychotic use among newly admitted residents of skilled nursing facilities: A population‐based study. (8th July 2018) - Jester, Dylan J.; Hyer, Kathryn; Molinari, Victor; Andel, Ross; Rozek, Ellen
Abstract : Objectives: To assess factors related to antipsychotic (AP) use in skilled nursing facilities for newly admitted residents aged 18 to 49, 50 to 64, 65 to 84, and 85 years or older. Methods: Retrospective, population‐level, Minimum Data Set (MDS) 2.0 data from the United States during the year of 2009 were used. Over 1 million residents were included. Fourteen clinically relevant variables were identified through a literature search. Antipsychotic use was defined as APs dispensed daily for the prior 7 days. Logistic regression was used to identify clinically relevant variables, which were then ranked based on magnitude of their association with APs. Results: Bipolar disorder and schizophrenia were consistently related to AP use across age groups. For older age groups, off‐label indications such as cognitive impairment, dementia, behavioral symptoms, and physical restraint use were more closely related to AP use, while delusions and hallucinations decreased in strength. Higher proportions of APs were found in all diseases and symptoms in nonelderly adults, with the exception of physical restraint use. Concurrent physical restraint and AP use was highest for older adults aged 65 to 84 at 36%. Conclusions: Correlates of AP use varied by age, with stronger associations between on‐label conditions and AP use among younger adults and off‐label conditions among older adults. Several less conventional determinants, namely, Parkinson disease, traumatic brain injury, and the use of physical restraints were identified to increase the likelihood of AP use. This study highlights the importance of monitoring for adverse effects for residents of all ages.